TEACHING WRITING USING MIND MAPPING STRATEGY TO THE 11TH STUDENTS OF SMAN 4 KEDIRI - Lilis Diah Wulandari; Dewi Kencanawati; Diani Nurhajati (JURNAL KOULUTUS, 2023)
Writing is one of the skills that is considered difficult for students when they learn English. The difficulties are developing ideas and composing sentences in English that will be expressed in their writing. For this reason, English teachers must have an interesting writing teaching strategy so that students are interested in learning to write. One strategy that can be applied is using Mind Mapping. The objectives of this study are: 1) to explain how Mind Mapping is applied in teaching writing; and 2) to describe the students' perceptions after being taught using this strategy. This study used a qualitative approach. The subjects of this study were one English teacher and four eleventh grade students, as representatives, of SMA 4 Kediri in the 2022/2023 academic year. The results showed that the steps in teaching writing skills using Mind Mapping were developing ideas, constructing sentences, arranging the sentences into a paragraph, and checking punctuation. Students' perceptions of the Mind Mapping strategy were positive, they felt writing became easier, especially in developing ideas and composing paragraphs.